FENOMENA FROZEN DEMOCRACY DI MESIR DARI TAHUN 2011-2013 (Fhenomenon of Frozen Democracy In Egypt Since 2011-2013) - Sahwal Abdul Haris (2014)
This research aimed at pursuing any information about factors to lead fhenomenon of frozen democracy in Egypt since 2011-2013. To analyze that writer adopted Robert A, Dhal concept about eigth indicators of democracy, Samuel P. Hutington concept about third wave of democracy and George Sorensen theory about frozen democracy. It was important to take note about why does democratization in Egypt seemed frozen. According to theoretical framework there were four indicators, first, economic instability. Second, stagnate of making civil cosiety. Third, Social and political did not ever direct to real consolidation. Fourth, ignore of regime legacy problems (corruption and human right). New phase of Egypt political face started since 25 January 2011, when Mubarak regime step down after thirty years at power.Soon, SCAF redesign electoral process to more open of political participation. As result first democratic electoral appeared and chosen Mursi as first civilian president in Egypt. After one year on his power, Mursi did not make any significant change. Directly, many Egyptian peoples down to the street and recall Mursi to step down from his power. Finally, 3 July 2013 Mursi down and be under arrest because of abuse of power during his year. The research resulted in explanation seemed that democratization in Egypt being frozen caused by incondusif situation. Furthermore, after Mursi couped by militer trough â€œsociety movementâ€, democracy still stagnate and does not ever appear to move forward to real solid democracy. Key word: frozen democracy, solid democracy, demoratization